Understanding the deep structure of the Essaouira basin using gravity data: hydrogeological inferences for a semiarid region in central-western Morocco - Khouz, Abdellah (2023)
The Essaouira Basin, located in central western Morocco, faces a significant threat of water shortage due to both the substantially reduced rainfall caused by climate change and the continuously increasing demand for this essential resource. Groundwater resources are being increasingly exploited to meet the needs of the population, whether for agricultural or domestic purposes. Therefore, it has become necessary to intensify investigations across the entire basin, particularly through indirect methods such as geophysical techniques, to accurately delineate the productive zones. In this context, the present study was undertaken to investigate the deep structure of this basin with the aim of comprehending the functioning of its aquifer system. This study is based on the interpretation of gravity data covering the Essaouira Basin. In addition to their qualitative analysis, these data underwent a methodological approach involving transformations to extract meaningful insights. The observed anomalies were interpreted in terms of (i) thickness variations within the slightly folded sedimentary series of the basin; (ii) Paleozoic basement topography; and (iii) the presence of salt deposits. In fact, among the negative anomalies, some coincide with evaporitic deposits that are known either from the geological outcrops or the seismic surveys carried out in the Essaouira Basin within the framework of petroleum exploration programs, while others coincide with areas of increased thickness of sedimentary sequences. The latter include synclines and basement depressions, where the accumulation of groundwater tends to occur; as a result, they constitute suitable zones for the drilling of water extraction wells. Groundwater flows observed in some existing wells are consistent with this hypothesis. The results of the contact analysis approach implemented within the framework of the study reveals the Essaouira Basin is affected by a fault network whose main direction is parallel to the Atlantic margin (i.e., NNE–SSW). This implies that the extensional tectonic phase responsible for initiating the rifting of the Central Atlantic in the Triassic era has primarily impacted the structural configuration of this basin. This study demonstrates the strong potential of the gravity method as a tool to delineate the deep structure of sedimentary basins and to identify potentially productive groundwater zones. The final results will provide important support to decision makers in sustainable groundwater management, especially in vulnerable areas.